Control interno y su incidencia en la gestión operativa de la compañía de servicios de taxis “villaprado & asociados” taxvilpra s.a. del cantón Santa Elena del año 2023 - Tubay Vergara, Karina Estefania (2025)
The importance of having a good internal control system in companies or businesses has increased in recent years, due to how practical it is to measure efficiency and productivity when implementing them; especially if it focuses on the basic activities they carry out, since they depend on it to stay in the market. The purpose of this research work is to evaluate the internal control system and its impact on the operational management of the Taxi Services Company 'VILLAPRADO & ASOCIADOS' TAXVILPRA S.A. of the Canton Santa Elena, year 2023.